Highly emissive organic solids with remarkably broad color tunability based on N, C-chelate, four-coordinate organoborons. Issue 89 (21st September 2015) - Shaikh, Aslam C.; Ranade, Dnyanesh S.; Thorat, Shridhar; Maity, Arunava; Kulkarni, Prasad P.; Gonnade, Rajesh G.; Munshi, Parthapratim; Patil, Nitin T.
Abstract : Herein reported are molecular fluorophores based on N, C -chelate, four-coordinate organoborons which exhibit tunable solid-state emission colors that cover the whole visible region from blue to red. Abstract : Molecular fluorophores based on N, C -chelate, four-coordinate organoborons exhibit tunable solid-state emission colors that cover the whole visible region from blue to red. The emission color can be tuned through the substituents on either quinolines or the boron center.